Countersinking the Lag Screw or Blade During Cephalomedullary Nailing of Geriatric Intertrochanteric Femur Fractures: Less Collapse and Implant Prominence Without Increased Cutout Rates. Issue 1 (1st January 2022) - Henry Goodnough, L.; Wadhwa, Harsh; Tigchelaar, Seth S.; Pfaff, Kayla; Heffner, Michael; van Rysselberghe, Noelle; DeBaun, Malcolm R.; Gardner, Michael J.; Bishop, Julius A.
Abstract : Introduction: The lag screw or helical blade of a cephalomedullary nail facilitates controlled collapse of intertrochanteric proximal femur fractures. However, excessive collapse results in decreased hip offset and symptomatic lateral implants. Countersinking the screw or helical blade past the lateral cortex may minimize subsequent prominence, but some surgeons are concerned that this will prevent collapse and result in failure through cutout. We hypothesized that patients with countersunk lag screws or helical blades do not experience higher rates of screw or blade cutout and have less implant prominence after fracture healing. Methods: A retrospective review of 175 consecutive patients treated with cephalomedullary nails for AO/OTA 31A1-3 proximal femur fractures and a minimum 3-month follow-up and 254 patients with a 6-week follow-up at a single US level I trauma center. Patients were stratified based on countersunk versus noncountersunk lag screw or helical blade in a cephalomedullary nail. The primary outcome was the cutout rate at minimum 3 months, and the secondary outcome was radiographic collapse at minimum 6 weeks. Results: Cutout rates were no different in patients with countersunk and noncountersunk screws and blades, and countersinking was associated with less collapse and less implant prominence at 6 weeks. Discussion: Surgeons can countersink the lag screw or blade when treating intertrochanteric proximal femur fractures with a cephalomedullary nail without increasing failure rates and with the potential benefits of less prominent lateral implants and decreased collapse.